Uric Acid and Impairment of Renal Function in Non-diabetic Hypertensive Patients - Hung, Yi-Hsin; Huang, Chin-Chou; Lin, Liang-Yu; Chen, Jaw-Wen (Frontiers in Medicine, 2022)
Hyperuricemia is a risk factor for renal impairment. However, investigations focusing on patients with hypertension are limited and inconsistent. A single-center prospective cohort study of 411 Han Chinese non-diabetic hypertensive patients was conducted in Taiwan. The mean age of the participants was 62.0 ±14.4 years. The baseline estimated glomerular filtration rate and uric acid level were 86 mL/min/1.73 m2 and 6.2 mg/dL, respectively. All patients underwent serum biochemistry tests for creatinine levels every 3 months. Renal events were defined as >25% and >50% decline in estimated glomerular filtration rate. During an average follow-up period of 4.7 ± 2.9 years (median 4.0 years), a >25 and >50% decline in estimated glomerular filtration rate was noted in 52 and 11 patients, respectively. The multivariate Cox regression analysis revealed that a baseline uric acid level ≥8.0 mg/dL increased the risk of >25% decline (hazard ratio: 3.541; 95% confidence interval: 1.655–7.574, P = 0.001) and >50% decline (hazard ratio: 6.995; 95% confidence interval: 1.309–37.385, P = 0.023) in estimated glomerular filtration rate. Similarly, a baseline uric acid level ≥7.5 mg/dL was independently associated with >25% decline (hazard ratio: 2.789; 95% confidence interval: 1.399–5.560, P = 0.004) and >50% decline (hazard ratio: 6.653; 95% confidence interval: 1.395–31.737, P = 0.017). However, this was not demonstrated at baseline uric acid level ≥7.0 mg/dL. Our study suggests that hyperuricemia is an independent risk factor for the decline in renal function in patients with hypertension. Uric acid level ≥7.5 mg/dL may be considered as the optimal cutoff value for clinical practice in predicting the development of renal impairment.